Engagement and disengagement with sustainable development : further conceptualization and evidence of validity for the Engagement/Disengagement in Sustainable Development Inventory (EDiSDI) - Moreira, Paulo (2022)
Engagement is a multidimensional construct with emotional, cognitive, and behavioral components. As a process, engagement captures how subjective experiences result from interactions between perceptions, information-processing and ecological influences in a way that activates internal states to maintain behavior. This process underlies the way people relate to different contexts, topics or issues. Engagement is highly responsive to contextual factors and a good predictor of desirable outcomes. Therefore, engagement with sustainable development has strong potential as a locus for intervention and research addressing sustainable development issues. However, research on engagement (and disengagement) with sustainable development is nascent and there is a need to bolster evidence on the psychometric adequacy of its associated measure. In this study, we analyzed data from four independent samples, all of which completed the Engagement/Disengagement with Sustainable Development Inventory (EDiSDI). The study has five major findings: (1) A bifactor model was replicated in multiple samples, thus confirming structural validity. (2) EDiSDI scores correlated with related constructs in a theoretically consistent manner, thus confirming convergent validity. (3) EDiSDI scores predicted variance in pro-sustainability behavior, hence demonstrating predictive validity. (4) The EDiSDI had measurement invariance across age, society, and gender. (5) A general factor reflecting engagement accounted for the majority of variance in items designed to measure various constructs that capture the way humans relate to sustainable development issues. A major contribution of this study is that it supports an integrative framework for conceptualizing two major expressions of how people relate to sustainable development: engagement and disengagement. Future research can use the EDiSDI to build knowledge on how engagement and disengagement can explain sustainable and unsustainable (e.g. negationist) behavioral patterns. This will be important for helping inform policies and practices for promoting sustainable behavioral patterns in citizens of different societies.